Observation of the strain-driven charge-ordered state in La0.7Ca0.3MnO3-d thin film with oxygen deficiency: Электpонные свойства металлов и сплавов - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Svetchnikov, V.L.; Zandbergen, H.W.; Lee, Y.P.; Park, J.S.; Kim, K.W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The magnetic and transport properties of La0.7Ca0.3MnO3-d films with an oxygen deficiency (d≃ 0.1) and a La0.9Ca0.1MnO3 film with the stoichiometric oxygen content are investigated in a wide temperature range. It is shown that the charge-ordered insulating (COI) state is observed for a La0.7Ca0.3MnO2.9 film with thickness d ≤ 30 nm, which manifests mainly a cubic crystal structure with an anomalously small lattice parameter for this composition. An increase in the film thickness (d ≃ 60 nm) leads to a structural transition from the lattice-strained cubic to the relaxed rhombohedral phase, is accompanied by a shift of the Curie point (TC) to lower temperature and a frustration of the COI state. The magnetic and transport properties of the La0.7Ca0.3MnO2.9 film with d ≃ 60 nm are similar to those exhibited by the optimally oxygen-doped La0.9Ca0.1MnO3 film. It is concluded that the formation of the COI state in the La0.7Ca0.3MnO3-d compound is governed by a compression of the crystal lattice rather than accumulation of oxygen vacancies, the low doping of the substituted divalent ions, or electronic phase separation.